UBE3A promotes foam cell formation and counters remyelination by targeting ABCA1 for proteasomal degradation - Loix, Melanie; Vanherle, Sam; Bolkaerts, Laura; Verberk, Sanne G. S.; Punt, Mattijs; Wouters, Flore; Moonen, Brecht; Verhagen, Rob; Van Wouw, Suzanne A. E.; Jongejan, Aldo; Distel, Ben; Elgersma, Ype; et al. (Nature communications, 2025)
The accumulation of foamy macrophages is a pathological hallmark of demyelinating brain disorders. Perturbed metabolism and efflux of intracellular lipids underlie the development of a harmful foamy macrophage phenotype in these disorders, yet, the molecular mechanisms underlying this dysregulation are poorly understood. Here, we show that the ubiquitin-proteasome system controls the turnover of the cholesterol efflux transporter ATP-binding cassette A1 (ABCA1) in lipid-loaded macrophages in the brain. We report that accumulation of myelin-derived lipids promotes the abundance and activity of ubiquitin-protein E3 ligase A (UBE3A) in macrophages, which stimulates ABCA1 ubiquitination and subsequent degradation. This boosts cellular lipid accumulation and induces an inflammatory macrophage phenotype that impairs remyelination. We further establish Tat-interacting protein 30 (TIP30), an inhibitor of importin β-mediated nuclear import, as an essential regulator of cytosolic UBE3A levels. Together, our findings identify UBE3A as a driver of foam cell formation and indicate that targeting UBE3A-mediated ABCA1 degradation is a promising strategy to enhance central nervous system repair. Foamy macrophages are a pathological hallmark of demyelinating brain disorders. Here, the authors identify the molecular mechanisms underlying the faulty regulation of lipid efflux that cause accumulation, suggesting a promising strategy to enhance central nervous system repair.